Dampak Inflasi terhadap Daya Beli Wisatawan dan Kinerja Industri Perhotelan dalam Perspektif Ekonomi Makro - Windi Firdaus; Noval Febriansyah; Abdul Azis Alhalim; M. Yusuf Bahtiar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Inflation is a macroeconomic indicator that significantly impacts economic activity, including the tourism and hospitality sectors. This study aims to analyze the impact of inflation on tourists' purchasing power and its implications for the performance of the hospitality industry from a macroeconomic perspective. Rising inflation tends to reduce people's purchasing power because the prices of goods and services, including transportation, accommodation, and tourism services, increase. This decline in purchasing power can affect tourists' travel decisions, potentially reducing tourism demand and hotel occupancy rates. In a macroeconomic context, price stability and economic growth are important factors influencing tourism demand and the performance of the hospitality sector. Several empirical studies have shown that macroeconomic variables such as inflation, gross domestic product (GDP), exchange rates, and interest rates are closely related to the development of the tourism industry and hotel performance. When inflation increases significantly, hotel operating costs such as energy, food, and labor also increase, which can ultimately reduce the profitability and operational efficiency of hotel companies. Therefore, stable inflation management is a crucial factor in maintaining the sustainability of the tourism and hospitality sectors. This study shows that macroeconomic stability plays a crucial role in maintaining tourists' purchasing power and improving the long-term performance of the hospitality industry.